A Review of National Policies, Programmes and Initiatives on Sustainable Urban Development in Nigeria - Alabi, Moruf; Raheem, W. M.; Bako, A. I. (NIU Journal of Social Sciences, 2018)
The unprecedented growth of urban centers in Nigeria in the recent time has been of great concerns to government and development agencies. Although, cities serve as ‘engines’ of growth in most developing countries by providing opportunities for employment, education, and ready markets for industrial and agricultural products, their phenomenal growth is not without its accompanied problems, such as high birth rates, high unemployment and or underemployment, high rate of crime, disintegrating or lack of infrastructural facilities and the growth of slums and squatter settlements. This paper is a review of national policies, programmes and initiatives on urban development in Nigeria. The management of urban growth for sustainable livability has seen the three-tiers of government (federal, state and local), engaged several ways to create vibrant urban centres that will attract jobs, foster economic development, and create attractive places for people to live, work and recreate. These include policies on housing, infrastructure and services, urban renewal and slum upgrading and environment, health and security among others. However, several of these policies have hit the rock at one stage or the other due to several factors, among which are ineffective institutional framework for planning, dearth of basic planning data and the declining economic base and fiscal resources resulting in paltry budgetary allocation. The paper concludes that urban development in Nigeria has been generally more politically motivated than demand driven. Inadequate funding, weak monitoring and evaluation mechanism, as well as lack of transparency, accountability and inclusive participation bedeviled the various policies and programme put in place. Keywords: Sustainable Development, Urban Growth, Policies, Environment, Programme